Strategi Komunikasi Dinas Komunikasi dan Informatika Kabupaten Batang dalam Menangkal Hoaks - Arifa Rachma Febriyani; Rintulebda Anggung Kaloka (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
The Batang Regency Government has held an Anti Hoax Declaration in 2017. However, the problem of spreading hoaxes on social media still continues. Even in the midst of a pandemic situation, hoaxes about COVID-19 have also caused public unrest. This study aims to describe the communication strategy of the Communication and Information Office of Batang Regency in warding off hoaxes. This research is a qualitative descriptive study. Data was collected by means of in-depth interviews and document review. The results of the study indicate that the Batang Regency Communication and Information Office seeks to improve digital community literacy by holding group discussion forums, socialization to high schools, anti-hoax digital campaigns on social media, and public service advertisements on regional radio. The communication strategy is not optimal because it is not based on careful planning and analysis. Another obstacle faced is the limited number of human and technological resources.